The protective activity of genistein against bone and cartilage diseases - Wu, Zhenyu; Liu, Luying (Frontiers in Pharmacology, 2022)
Genistein, a natural isoflavone rich in soybean and leguminous plants, has been shown various biological effects, such as anti-inflammation, anti-oxidation, anti-cancer, and bone/cartilage protection. Due to the structural similarity to estrogen, genistein exhibits estrogen-like activity in protecting against osteoporosis and osteoarthritis. Furthermore, genistein has been considered as an inhibitor of tyrosine kinase, which has been found to be dysregulated in the pathological development of osteoporosis, osteoarthritis, and intervertebral disc degeneration (IDD). Many signaling pathways, such as MAPK, NF-κB, and NRF2/HO-1, are involved in the regulatory activity of genistein in protecting against bone and cartilage diseases. The potential molecular mechanisms of genistein in therapeutic management of bone and cartilage diseases have been investigated, but remain to be fully understood. In this article, we mainly discuss the current knowledge of genistein in protecting against bone and cartilage diseases, such as osteoporosis, osteoarthritis, rheumatoid arthritis (RA), and IDD.